Postnatal nutrition environment reprograms renal DNA methylation patterns in offspring of maternal protein-restricted stroke-prone spontaneously hypertensive rats - Ando, Chika; Ma, Sihui; Miyoshi, Moe; Furukawa, Kyohei; Li, Xuguang; Jia, Huijuan; Kato, Hisanori (Frontiers in Nutrition, 2023)
Maternal malnutrition hampers the offspring health by manipulating the epigenome. Recent studies indicate that the changes in DNA methylation could be reversed by afterbirth nutrition supplementation. In this study, we used DNA methylation arrays to comprehensively investigate the DNA methylation status of the renal promoter regions and the effects of postnatal protein intake on DNA methylation. We fed stroke-prone spontaneously hypertensive (SHRSP) rat dams a normal diet or a low-protein diet during pregnancy, and their 4-week-old male offspring were fed a normal diet or a high-/low-protein diet for two weeks. We found that the methylation status of 2,395 differentially methylated DNA regions was reprogrammed, and 34 genes were reset by different levels of postnatal protein intake in the offspring. Among these genes, Adora2b, Trpc5, Ar, Xrcc2, and Atp1b1 are involved in renal disease and blood pressure regulation. Our findings indicate that postnatal nutritional interventions can potentially reprogram epigenetic changes, providing novel therapeutic and preventive epigenetic targets for salt-sensitive hypertension.